«Great geographical discoveries»: the meaning and historical content of the term in the light of the interaction experience of civilizations in the New World - Ya. G. Shemyakin (Ибероамериканские тетради)
The main question that Humankind was confronted with at the beginning of the Age of Great Discoveries can be spelled out as follows: «Just how is the world shaped?» The subsequent Great Geographical Discoveries showed the true dimension and structure of the surface of the Planet, as well as the real range of diversity of the «World of Humans». And the new knowledge of the shape of the world, in turn, gave rise to the following dilemma: can we surmise any unity of this world, all the great diversity of human cultures notwithstanding, or is such a unity nothing but an illusion? The search for an answer to this question constituted one of the axes of the spiritual life of Humankind in subsequent centuries up to the present day. The crucial point in the search for an answer to the above said question was the Discovery of America. The Meeting of two Worlds brought about the most acute crisis of consciousness on both sides. In the course of ensuing attempts at overcoming the crisis, they discovered new dimensions of their own heritage and new prospects for future life. Two alternative ways of evolution of homo sapiens, essentially different and even opposed, took shape. On the one hand, it was globalization, and on the other hand, it was increased emphasis on the heterogeneity of specific human communities at different levels, being the regional civilizations the most conspicuous ones in this respect. The collision, interweaving and mutual influence of those processes predetermined the main trends of human history over the past five centuries. In Latin America, a special frontier civilizational type has developed, as different from the classical both Western and Oriental models. It embodies more patently the principle of dialogue, which is, according to M. Bakhtin, a distinctive feature of the evolution of homo sapiens in general. This type of civilisation acquires particular importance at the present stage of evolution of the human world, which, on the threshold of the XXI century has entered its new stage, that of uncertainty and instability, the frontier stage.